Techniques for Counting and Tracking the Spatial and Temporal Movement of Visitors - Xia, Jianhong (Cecilia); Arrowsmith, C. (The University of Arizona Press, 2008)
Data collection can become an overwhelmingtask for the simulation modeler and,indeed, can become the single most importantfactor that restricts the development and ultimateuse of that model. This chapter serves as aresource for the simulation modeler to assist indetermining what data is required and whattechniques and technologies are currently available.The chapter discusses the data requiredfor describing the spatial and-temporal movementof visitors. A review of the techniques forthe tracking and counting of visitor movements atvarious spatial scales will be undertaken andeach method will be assessed for its suitability asa mechanism for acquiring data for simulationmodeling. These techniques are summarizedassessing their advantages and disadvantagesand suitable corresponding applications.